2015
DOI: 10.1016/j.bjane.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Colloids versus crystalloids in objective-guided fluid therapy, systematic review and meta-analysis. Too early or too late to draw conclusions

Abstract: Because of the limitations of this meta-analysis due to the small number of randomized clinical trials and patients included, the results should be taken cautiously, and the performance of new randomized clinical trials is proposed, with enough statistical power, comparing balanced and unbalanced colloids to balanced and unbalanced crystalloids, following the protocols of GDFT, considering current guidelines and suggestions made by groups of experts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Cochrane database analysis showed increased need for renal replacement therapy and increased mortality with use of starch solutions in critically ill patients . Another meta‐anlaysis found increased mortality with starch solutions without any increased need for RRT . A recent systematic review did not find any additional benefits with starch and hence recommended against its use in the perioperative setting .…”
Section: Discussionmentioning
confidence: 99%
“…Cochrane database analysis showed increased need for renal replacement therapy and increased mortality with use of starch solutions in critically ill patients . Another meta‐anlaysis found increased mortality with starch solutions without any increased need for RRT . A recent systematic review did not find any additional benefits with starch and hence recommended against its use in the perioperative setting .…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis found that there was no difference in postoperative complications when using either crystalloids or colloids; however, GDFT with colloids was associated with a trend toward increased mortality. 67 Continued debate exists surrounding the appropriate fluid type in GDFT and ERAS protocols. Due to their ability to increase intravascular volume more reliably and for a longer period of time than crystalloids, colloids have earned a place in many ERAS pathways.…”
Section: Fluid Typementioning
confidence: 99%
“…Recent meta‐analyses suggest a slightly increased risk of mortality associated to HES administration to critically ill patients, mainly linked to higher doses of HES or daily fluid balance, and influenced by baseline comorbidity . Mortality shows as a rather late finding with separation of survival curves occurring around day 20 .…”
Section: Current Published Human Research Information and Datamentioning
confidence: 99%